Associations between Listeria monocytogenes genomic characteristics and adhesion to polystyrene at 8 °C. (April 2022) - Mahoney, David Burke James; Falardeau, Justin; Hingston, Patricia; Chmielowska, Cora; Carroll, Laura M.; Wiedmann, Martin; Jang, Sung Sik; Wang, Siyun
Abstract: Listeria monocytogenes remains a threat to the food system and has led to numerous foodborne outbreaks worldwide. L. monocytogenes can establish itself in food production facilities by adhering to surfaces, resulting in increased resistance to environmental stressors. The aim of this study was to evaluate the adhesion ability of L. monocytogenes at 8 °C and to analyse associations between the observed phenotypes and genetic factors such as internalin A ( inlA ) genotypes, stress survival islet 1 (SSI-1) genotype, and clonal complex (CC). L. monocytogenes isolates (n = 184) were grown at 8 °C and 100% relative humidity for 15 days. The growth was measured by optical density at 600 nm every 24 h. Adherent cells were stained using crystal violet and quantified spectrophotometrically. Genotyping of inlA and SSI-1, multi-locus sequence typing, and a genome-wide association study (GWAS) were performed to elucidate the phenotype-genotype relationships in L. monocytogenes cold adhesion. Among all inlA genotypes, truncated inlA isolates had the highest mean adhered cells, ABS595nm = 0.30 ± 0.15 (Tukey HSD; P < 0.05), while three-codon deletion inlA isolates had the least mean adhered cells (Tukey HSD; P < 0.05). When SSI-1 was present, more cells adhered; less cells adhered when SSI-1 was absent (Welch's t -test; P < 0.05). Adhesion was associated with clonal complexes which have low clinical frequency, while reduced adhesion was associated with clonal complexes which have high frequency. The results of this study support that premature stop codons in the virulence gene inlA are associated with increased cold adhesion and that an invasion enhancing deletion in inlA is associated with decreased cold adhesion. This study also provides evidence to suggest that there is an evolutionary trade off between virulence and adhesion in L. monocytogenes . These results provide a greater understanding of L. monocytogenes adhesion which will aid in the development of strategies to reduce L. monocytogenes in the food system. Graphical abstract: Image 1 Highlights: Truncated inlA, SSI-1, and group B CC strains associated with increased adhesion. 3CD inlA, no SSI-1, and group A CC strains associated with decreased adhesion. Adhesion and virulence evolutionary trade – off in L. monocytogenes. Novel 47 amino acid deletion in inlB B repeats region.